Adipose tissue gene expression of CXCL10 and CXCL11 modulates inflammatory markers in obesity: implications for metabolic inflammation and insulin resistance. (June 2020) - Kochumon, Shihab; Madhoun, Ashraf Al; Al-Rashed, Fatema; Azim, Rafaat; Al-Ozairi, Ebaa; Al-Mulla, Fahd; Ahmad, Rasheed
Background: The CXCL subfamily of chemokines (CXCL9, CXCL10, and CXCL11; angiostatic chemokines) plays a key role in many inflammatory diseases. However, the expression of CXCLs in adipose tissue (AT) during obesity and association of these CXCLs with inflammatory markers and insulin resistance are poorly understood. Therefore, this study aimed to investigate the effects of CXCL gene expression on subcutaneous AT inflammatory markers and insulin resistance. Methods: Subcutaneous-fat biopsies were collected from 59 nondiabetic (lean/overweight/obese) individuals for RNA isolation. Expression levels of AT CXCL and inflammatory markers were determined by quantitative reverse transcriptase polymerase chain reaction (RT-qPCR). Biomedical parameters in the plasma were measured by enzyme-linked immunosorbent assay (ELISA). Insulin resistance was estimated using homeostatic model assessment (HOMA-IR). Results: AT CXCL expression was higher in obese compared with lean individuals ( p  < 0.05) and positively correlated with body mass index (BMI; r  ⩾ 0.269, p  < 0.05). Expression of CXCL9, CXCL10, and CXCL11 correlated significantly with various pro-inflammatory markers, including family members of interleukins, chemokines, and their prospective receptors ( r  ⩾ 0.339, p  ⩽ 0.009), but not anti-inflammatory markers. CXCL11 expression correlated specifically with the expression of CCL5, CCL18, TLR3, TLR4, TLR8, IRF5, and NF-κB ( r  ⩾ 0.279, p  ⩽ 0.039). Notably, CXCL11 was correlated with C-reactive protein (CRP), fasting blood glucose (FBG), and HOMA-IR. In multiple regression analysis, CXCL11 was identified as an independent predictor of CCL19, CCL5, IL-6, and TLR3. Conclusion: These data suggest that the CXCL family members, specifically CXCL10 and CXCL11, are potential biomarkers for the onset of AT inflammation during obesity.